Optimasi Suhu Pembuatan Arang Aktif Dari Ampas Kopi Terhadap Penurunan Kadar COD Dan BOD Pada Air Limbah Tahu - Adlin, Irman Ansari; Ismet, Rhahmasari; Amalia, Syara; Putri, Amanda; Jufrinaldi, Jufrinaldi (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
The tofu industry in Indonesia faces significant challenges in managing liquid waste, which typically contains high levels of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD), exceeding the government-set maximum limits. This study aims to explore the optimization of activated carbon-making temperature from coffee grounds and evaluate its ability to reduce COD and BOD levels in tofu industry wastewater. The methods used in this study include the preparation and characterization of activated carbon produced from coffee grounds with temperature variations from 150°C to 550°C. The results showed that the optimal temperature for preparing active carbon was 450°C, resulting in an active carbon yield of 32.56%. At this temperature, the measured water content was 2.96%, ash content was 2.96%, and iodine absorption was 787.24 mg/g, all of which met the standards of SNI No. 06-3730-1995. Evaluation of the impact of using the resulting activated carbon on tofu industry wastewater revealed a decrease in COD levels from 373.25 mg/L to 122.86 mg/L, corresponding to a 67% decrease, as well as a decrease in BOD levels from 191.65 mg/L to 20.02 mg/L, equivalent to an 89% decrease. These findings suggest that activated carbon derived from coffee grounds can be an effective and sustainable alternative for wastewater treatment, providing a more environmentally friendly waste management solution.